Death, loss, memory and mourning in the long Nineteenth Century, 1780-1914.
1 online resource (420 pages)
Keywords: This four-volume interdisciplinary collection explores loss, memory, and mourning in the long nineteenth century. Primary sources explore death and mourning from literary, spiritual, historical, and intellectual perspectives. Accompanied by extensive editorial commentary, this collection will be of great interest to students and scholars of the History of Emotions.